Is there a role of frozen section of sentinel lymph node in patients with early breast cancer for the management of axilla in India: a prospective study - Arora, Anshika; Chauhan, Neena; Saini, Sunil; Vishwakarma, Nishish; Luthra, Tanvi (International Surgery Journal, 2019)
Background: Evaluation of axilla using sentinel lymph node biopsy (SLNB) is the standard of care in node negative early breast cancer. Intra operative assessment of SLNB with frozen section (FS) often guides the surgeon regarding decision for level of axillary dissection. The aim of this study was to evaluate accuracy of FS of SLNB in these patients with histopathology examination (HPE) as the gold standard. Methods: This study was performed between July 2017 and November 2018. After gross evaluation of SLNB, nodes were cut in half and frozen; the other half was preserved for HPE. For FS, nodes were sectioned to 4 mm width and examined. Results: A total of 61 patients underwent SLNB, 55 patients undergoing intra-operative FS. The mean age was 53 years (range 30-84, ± 15.09 SD), primary tumor was clinically T1 in 23.6%, T2 in 76.4% patients. A median of four sentinel nodes were identified, mean size 13.84 mm. On FS SLNB was positive for metastasis in 14 (25.5%), on HPE in 16 (29.1%) patients. There were 13 true positive, 38 true negative, 3 false negative and 1 false positive result for FS. The sensitivity, specificity, positive and negative predictive value, false negative and false positive rates were 81.25%, 97.44%, 92.86%, 92.73%, 18.75% and 2.56% respectively in this study. The overall accuracy of FS of SLNB in early carcinoma breast was found to be 92.73%. Conclusions: An intra-operative FS of the SLN in node negative early breast cancer is a highly sensitive tool in axilla management.